One‐year mortality and consequences of COVID‐19 in cancer patients: A cohort study. Issue 10 (29th August 2021) - Chai, Chen; Feng, Xiaojun; Lu, Meixia; Li, Shoupeng; Chen, Kui; Wang, Hongxiang; Wang, Wendan; Tang, Zhaoming; Cheng, Gang; Wu, Xiaoxiong; Li, Yunfeng; Wen, Yuying; et al.
Abstract: The 1‐year mortality and health consequences of COVID‐19 in cancer patients are relatively underexplored. In this multicenter cohort study, 166 COVID‐19 patients with cancer were compared with 498 non‐cancer COVID‐19 patients and 498 non‐COVID cancer patients. The 1‐year all‐cause mortality and hospital mortality rates in Cancer COVID‐19 Cohort (30% and 20%) were significantly higher than those in COVID‐19 Cohort (9% and 8%, both P  < .001) and Cancer Cohort (16% and 2%, both P  < 0.001). The 12‐month all‐cause post‐discharge mortality rate in survival discharged Cancer COVID‐19 Cohort (8%) was higher than that in COVID‐19 Cohort (0.4%, P  < .001) but similar to that in Cancer Cohort (15%, P  = .084). The incidence of sequelae in Cancer COVID‐19 Cohort (23%, 26/114) is similar to that in COVID‐19 Cohort (30%, 130/432, P  = .13). The 1‐year all‐cause mortality was high among patients with hematologic malignancies (59%), followed by those who have nasopharyngeal, brain, and skin tumors (45%), digestive system neoplasm (43%), and lung cancers (32%). The rate was moderate among patients with genitourinary (14%), female genital (13%), breast (11%), and thyroid tumors (0). COVID‐19 patients with cancer showed a high rate of in‐hospital mortality and 1‐year all‐cause mortality, but the 12‐month all‐cause post‐discharge mortality rate in survival discharged cancer COVID‐19 patients was similar to that in Cancer Cohort. Comparing to COVID‐19 Cohort, risk stratification showed that hematologic, nasopharyngeal, brain, digestive system, and lung tumors were high risk (44% vs 9%, P  < 0.001), while genitourinary, female genital, breast, and thyroid tumors had moderate risk (10% vs 9%, P  = .85) in COVID‐19 Cancer Cohort. Different tumor subtypes had different effects on COVID‐19. But if cancer patients with COVID‐19 manage to survive their COVID‐19 infections, then long‐term mortality appears to be similar to the cancer patients without COVID‐19, and their long‐term clinical sequelae were similar to the COVID‐19 patients without cancer.